Prosedur pengembangan kurikulum (kajian literatur manajemen inovasi kurikulum) - Varary Mechwafanitiara Cantika (Himpunan Pengembang Kurikulum Indonesia (HIPKIN), 2022)
The curriculum plays an essential role in educational success. Quality education starts with a suitable and appropriate curriculum. The curriculum is also a necessary component of education. The curriculum must be changed and updated to face the demands of the times to create superior graduates or Human Resources (HR) who can compete globally. This research aims to find out the various forms of curriculum development procedures. The research method used is a literature review from different trusted sources or previous research. The study results indicate that curriculum experts apply various curriculum development procedures. When viewed from the perspective of curriculum innovation management, the guidelines for curriculum development include curriculum supervision, curriculum organization, staffing, and curriculum planning. The existence of curriculum innovation management can be the answer to changes in the demands of the direction of education, which are influenced by various factors that are later expected to be able to provide new experiences to students. AbstrakKurikulum memegang peranan yang penting dalam keberhasilan pendidikan dikarenakan pendidikan yang bermutu berawal dari kurikulum yang baik dan tepat. Perlu dilakukan perubahan serta pembaharuan pada kurikulum guna menghadapi tuntutan perkembangan zaman dalam upaya menciptakan Sumber Daya Manusia (SDM) unggul yang mampu bersaing secara global. Tujuan penelitian ini adalah mengetahui bentuk-bentuk prosedur pengembangan kurikulum yang beragam. Metode penelitian yang digunakan adalah kajian literatur dari berbagai sumber terpercaya atau penelitian terdahulu. Hasil penelitian menunjukkan bahwa terdapat berbagai prosedur pengembangan kurikulum yang diterapkan oleh para ahli kurikulum. Adapun prosedur pengembangan kurikulum apabila ditinjau dari segi manajemen inovasi kurikulum meliputi: pengawasan kurikulum; pengorganisasian kurikulum; penyusunan staf; dan perencanaan kurikulum. Keberadaan manajemen inovasi kurikulum dapat menjadi jawaban dari adanya perubahan tuntutan arah pendidikan yang dipengaruhi oleh berbagai faktor yang nantinya diharapkan juga mampu memberikan pengalaman baru kepada peserta didik.Kata Kunci: Kurikulum; pengembangan kurikulum; prosedur pengembangan kurikulum